TRANSITIVITY USED IN DONALD TRUMP INAUGURATION SPEECH - FADIA, BAIQ (LANGUAGE HORIZON, 2019)
ABSTRACT In political speech there are so many ideas that come from the speaker, like in inauguration speech of new president. Donald Trump is the new president of America, in his controversy winning speech there are ideology that shown during the speech. The aim of the researcher of this study is how the transitivity process reveal the ideology. The main theory of this research is Fairclough?s theoretical framework of CDA (1997) that influenced by Halliday (1994). This study used qualitative as a method, because the researcher think that the method was fi with the topic. The data was from (https://www.whitehouse.gov/briefings-statements/the-inaugural-address/) Transitivity has six types and during the speech Donald trump used the six types of processes but only three processes showed up the most. Those are material process, relational process, and behavioral process. The conclusion of this study is that participant of transitivity that Donald Trump used in the speech showing he put his work as the society priority, and to ask the USA society work about the resolution with him. While the ideology is make the society more convinced